MECHANISMS OF INTER-DIFFUSION REACTIONS DURING THE HEATING OF METALLIC LAYER CONTACT SYSTEMS - Grovenor, C (1982)
The process of diffusion-induced boundary migration (DIBM) is introduced, and its especial influence on layered thin film structures is discussed. Itis proposed that DIBM can cause extremely rapid mass transport of material in heated layer films. Three experimental systems are presented in which the process of DIBM can be observed, and the importance of such a process in conventional thin film technologies is briefly discussed. © 1982.